NMR Crystallography Reveals Carbonate Induced Al‐Ordering in ZnAl Layered Double Hydroxide. Issue 64 (25th October 2021) - Radhakrishnan, Sambhu; Lauwers, Karl; Chandran, C. Vinod; Trébosc, Julien; Pulinthanathu Sree, Sreeprasanth; Martens, Johan A.; Taulelle, Francis; Kirschhock, Christine E. A.; Breynaert, Eric
Abstract: Layered double hydroxides (LDHs) serve a score of applications in catalysis, drug delivery, and environmental remediation. Smarter crystallography, combining X‐ray diffraction and NMR spectroscopy revealed how interplay between carbonate and pH determines the LDH structure and Al ordering in ZnAl LDH. Carbonate intercalated ZnAl LDHs were synthesized at different pH (pH 8.5, pH 10.0, pH 12.5) with a Zn/Al ratio of 2, without subsequent hydrothermal treatment to avoid extensive recrystallisation. In ideal configuration, all Al cations should be part of the LDH and be coordinated with 6 Zn atoms, but NMR revealed two different Al local environments were present in all samples in a ratio dependent on synthesis pH. NMR‐crystallography, integrating NMR spectroscopy and X‐ray diffraction, succeeded to identify them as Al residing in the highly ordered crystalline phase, next to Al in disordered material. With increasing synthesis pH, crystallinity increased, and the side phase fraction decreased. Using 1 H− 13 C, 13 C− 27 Al HETCOR NMR in combination with 27 Al MQMAS, 27 Al‐DQ‐SQ measurements and Rietveld refinement on high‐resolution PXRD data, the extreme anion exchange selectivity of these LDHs for CO3 2− over HCO3 − was linked to strict Al and CO3 2− ordering in the crystalline LDH. Even upon equilibration of the LDH in pure NaHCO3 solutions, only CO3 2− was adsorbed by the LDH. This reveals the structure directing role of bivalent cations such as CO3 2− during crystallization of [M 2+ 4 M 3+ 2 (OH)2 ] 2+ [A 2− ]1 ⋅yH2 O LDH phases. Abstract : Smarter crystallography, combining X‐ray diffraction and NMR spectroscopy revealed how interplay between carbonate and pH determines the LDH structure and Al ordering in ZnAl LDH. This study reveals the structure directing role of bivalent cations such as CO3 2− during crystallization of [M 2+ 4 M 3+ 2 (OH)2 ] 2+ [A 2− ]1 ⋅yH2 O LDH phases.